The African Ant Leadership Paradigm in an inclusive Regional Quality Framework for Cross-Border Higher Education in the SADC region - Nyoni, Jabulani (African Perspectives of Research in Teaching & Learning, 2021)
The noble notion of the regional collective rationalisation of accreditation, quality assurance (QA) and audits within Southern Africa borders is affirmed by the desire to encourage adherence to quality assurance standards or protocols, that should result in believability and authenticity of university qualifications. The study employed a qualitative research approach, underpinned by an African ant leadership philosophical overview to analyse experiences and views of 12 university professoriates’ readiness to facilitative the smooth implementation of Southern African Development Community Qualifications Framework within Southern African Development Community region. I used Structured Online Mediated or Facilitated Conversations as a method and a computer as a tool to collect data. Thematic analysis was preferred to analyse data. Findings indicate that Southern African Development Community member university professoriates are hamstrung by archaic colonial self-caging and partitioning quality assurance audit modalities that promote so-called “institutional independence” over the prioritisation of regional “collective independence”. I propose that Southern African Development Community universities’ academic bodies should prioritise the establishment of an independent inclusive Communalities of Regional Quality Framework body that will craft a quality assurance audits design model to be used by higher education institutions to benchmark educational programmes. I further posit that the persistent employment of self-caging, colonially inherited quality assurance frameworks that continue to compartmentalise Southern African Development Community higher education institutions within the confines of colonially drawn borders denies all in sundry equal education opportunities and promotes regional exclusion. Keywords: Quality assurance audits, African ant leadership approach, communalities of ethical peer review, de-borderisation of quality assurance protocols
African Perspectives of Research in Teaching & Learning (APORTAL) Vol 5(1): (2021)
Keywords: Quality assurance audits; African ant leadership approach; Communalities of ethical peer review; De-borderisation of quality assurance protocols; Quality assurance - Standards; African -- Education (Higher)